2023
DOI: 10.3390/molecules28052035
|View full text |Cite
|
Sign up to set email alerts
|

Hematite: A Good Catalyst for the Thermal Decomposition of Energetic Materials and the Application in Nano-Thermite

Abstract: Metal oxides (MOs) are of great importance in catalysts, sensor, capacitor and water treatment. Nano-sized MOs have attracted much more attention because of the unique properties, such as surface effect, small size effect and quantum size effect, etc. Hematite, an especially important additive as combustion catalysts, can greatly speed up the thermal decomposition process of energetic materials (EMs) and enhance the combustion performance of propellants. This review concludes the catalytic effect of hematite w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 132 publications
0
7
0
Order By: Relevance
“…Commonly used combustion promoters include metals and their oxides, energetic complexes, carbon materials, nanocomposites, carbon-based composite materials, etc. [6][7][8][9][10][11][12] Among them, energetic complexes (ECs) based on the coordination selfassembly of metal ions and nitrogen-rich ligands have the advantages of a high energy level, a large specific surface area and high gas production, thus receiving widespread attention in the field of energetic materials and combustion promoters. 9,[13][14][15][16][17][18][19][20][21] In the process of research, however, ECs gradually showed the shortcomings of poor conductivity, thermal conductivity and safety performance.…”
Section: Introductionmentioning
confidence: 99%
“…Commonly used combustion promoters include metals and their oxides, energetic complexes, carbon materials, nanocomposites, carbon-based composite materials, etc. [6][7][8][9][10][11][12] Among them, energetic complexes (ECs) based on the coordination selfassembly of metal ions and nitrogen-rich ligands have the advantages of a high energy level, a large specific surface area and high gas production, thus receiving widespread attention in the field of energetic materials and combustion promoters. 9,[13][14][15][16][17][18][19][20][21] In the process of research, however, ECs gradually showed the shortcomings of poor conductivity, thermal conductivity and safety performance.…”
Section: Introductionmentioning
confidence: 99%
“…1–4 Recent studies demonstrated that fundamental properties of bulk materials can be effectively improved and customized by tuning the size, shape, composition, and crystallinity in nanomaterials. 3–9 Hematite is an environmentally compatible, cost-effective, and good corrosion-resistive narrow band gap semiconductor. These striking properties led to the fabrication of various nanostructures of hematite ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…These striking properties led to the fabrication of various nanostructures of hematite ( e.g. , nanorods, nanotubes, nanocubes, nanospheres, and nanoflakes) by employing a variety of synthesis methods to allow for major applications in magnetic storage devices, 10 biomedicine, 11 engineering and industrial fields, 3 lithium-ion batteries, 12 gas sensors, 13 water treatment, 14 and magnetic resonance imaging (MRI). 15 However, the physical property of these nanomaterials strongly depend on the size, shape, and crystallinity, which are dependent on the synthesis method.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations